Thrombalexin: Use of a Cytotopic Anticoagulant to Reduce Thrombotic Microangiopathy in a Highly Sensitized Model of Kidney Transplantation. Issue 8 (23rd March 2017) - Manook, M.; Kwun, J.; Burghuber, C.; Samy, K.; Mulvihill, M.; Yoon, J.; Xu, H.; MacDonald, A. L.; Freischlag, K.; Curfman, V.; Branum, E.; Howell, D.; et al.
Abstract : Early activation of coagulation is an important factor in the initiation of innate immunity, as characterized by thrombotic microangiopathy (TMA). In transplantation, systemic anticoagulation is difficult due to bleeding. A novel "cytotopic" agent, thrombalexin (TLN), combines a cell‐membrane‐bound (myristoyl tail) anti‐thrombin (hirudin‐like peptide [HLL]), which can be perfused directly to the donor organ or cells. Thromboelastography was used to measure time to clot formation (r‐time) in both rhesus and human blood, comparing TLN versus HLL (without cytotopic tail) versus negative control. Both TLN‐ and HLL‐treated rhesus or human whole blood result in significantly prolonged r‐time compared to kaolin controls. Only TLN‐treated human endothelial cells and neonatal porcine islets prolonged time to clot formation. Detection of membrane‐bound TLN was confirmed by immunohistochemistry and fluorescence activated cell sorter. In vivo, perfusion of a nonhuman primate kidney TLN‐supplemented preservation solution in a sensitized model of transplantation demonstrated no evidence of TLN systemically. Histologically, TLN was shown to be present up to 4 days after transplantation. There was no platelet deposition, and TMA severity, as well as microvascular injury scores (glomerulitis + peritubular capillaritis), were less in the TLN‐treated animals. Despite promising evidence of localized efficacy, no survival benefit was demonstrated. Abstract : Direct local treatment of the transplanted kidney with thrombalexin, a cytotopic antithrombin agent, reduces histological evidence of thrombotic microangiopathy in a sensitized model of nonhuman primate transplantation.